Natural Product Erianin Inhibits Bladder Cancer Cell Growth by Inducing Ferroptosis via NRF2 Inactivation - Xiang, Yu; Chen, Xiaying; Wang, Wengang; Zhai, Lijuan; Sun, Xueni; Feng, Jiao; Duan, Ting; Zhang, Mingming; Pan, Ting; Yan, Lili; Jin, Ting; Gao, Quan; et al. (Frontiers in Pharmacology, 2021)
Erianin, a natural product derived from Dendrobium chrysotoxum Lindl, has been reported to exert antitumor activity in various cancer types. However, the effects and molecular mechanisms of erianin in bladder cancer cells remain unexplored. In this study, we found that erianin triggered cell death and cell cycle arrest in bladder cancer cells. Subsequently, we demonstrated that erianin could promote the accumulation of lethal lipid-based reactive oxygen species (ROS) and the depletion of glutathione (GSH), suggesting the induction of ferroptosis. In the further study, the ferroptosis inhibitor deferoxamine (DFO), N-Acetylcysteine (NAC) and GSH but not necrostatin-1, CQ or Z-VAD-FMK rescued erianin-caused cell death, indicating ferroptosis played a major role in erianin-caused cell death. In vivo, we also showed that erianin suppressed the tumor growth by inducing ferroptosis. Mechanistically, we demonstrated that Nuclear factor E2-related factor 2 (NRF2) inactivation was a key determinant for erianin-caused ferroptosis. The compound Tert-butylhydro-quinone (TBHQ), an activator of NRF2, suppressed erianin-induced ferroptosis in bladder cancer cells. Whereas, NRF2 inhibition by shRNA augmented the ferroptosis response induced by erianin treatment. In conclusion, our data provide the first evidence that erianin can trigger lipid peroxidation and ferroptosis-like cell death in bladder cancer, which will hopefully provide a promising anticancer compound for bladder cancer treatment.